Penyelesaian Sengketa Kontrak Modal Ventura Dengan Perusahan Pasangan Usaha (PPU) - Indrajaya Indrajaya (Universitas Batanghari Jambi, 2020)
In running their business, what is often the main obstacle for business actors in developing their business is usually related to the provision of capital. In order to overcome this, the Government issued policies in the economic sector, one of which was the issuance of policies regarding Financing Institutions as regulated in Presidential Regulation Number 9 of 2009. Followed up by the Regulation of the Minister of Finance on Venture Capital Companies No. 18 of 2012. As one of the businesses in the financial services sector, its approach is not only in business but also needs to be accompanied by a legal approach (legal approch) so that its existence can be recognized in business traffic. Even though the agreement has been bound in a contract, it is still common for business partner companies to default, and even lead to disputes in court. The purpose of this study is to analyze the settlement of disputes due to default by PPU on the contents of the financing contract between the Venture Capital Company and the PPU. The research method is normative legal research, using primary legal materials, secondary legal materials and tertiary legal materials. The approach is carried out with a statutory approach (statute approach) and a conceptual approach (conceptual approach). From the results of the research it is known that the settlement of disputes due to default by PPU on the contents of the financing contract between the Venture Capital Company and PPU, the settlement of the dispute is carried out by prioritizing non-litigation mechanisms, but if no agreement is reached, the Litigation channel is used.